Management Of Ompok Pabo Brooders - A Pre Requisite Strategy For Captive Breeding - D. SARMA,; J. DAS,; A. DUTTA, (International Journal of Pharma and Bio Sciences, 2012)
Present investigation deals with management of Ompok pabo brooders up to maturity for the period of December/2007 to November/2010. Brood fishes of the sizes 12 to 16 cm in total length and 22.19gm to 25.20gm were collected, released and cultured in the polyculture pond with proper management. Essential water quality parameters were monitored regularly and corrected during the period of study. Brooders were fed with earth worm, formulated food, live & trash small fishes, formulated pellet of mixed silk worm pupae and rice polish in appropriate rate and ratio. Maturity was attained at the age of about one year in the stocking pond after rearing for six months. Fully matured brood fishes were measured 21.0 cm to 23.7 cm in total length and 65.0 gm to 75.0 gm in weight. Sexual dimorphism of Males and females could be fully distinguishable from the month of May onwards.